PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN SERVICE EXCELLENT TERHADAP PELAYANAN PEMBUATAN KTP-EL DI DKI JAKARTA UNTUK MENINGKATKAN INDEKS KEPUASAN MASYARAKAT - Woroutama, Ryfaldo; Derriawan, Derriawan; Putriana, Lies (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
The purpose of this study was to determine the effect of human resource development in improving service excellence for KTP-EL making services in DKI Jakarta to increase the community satisfaction index. This study uses quantitative and qualitative (mixed) research methods. The sampling technique uses the Non Probability Sampling technique and the accidental sampling technique. Data collection using a questionnaire. Data analysis techniques used Structural Equation Modeling (SEM) analysis which was processed with Smart PLS 3.0 for quantitative analysis, while for qualitative analysis using the interview method. Quantitative research results prove that competent human resources, facilities and infrastructure and service quality each influence service excellent, while service excellent also has a large influence on community satisfaction.